Sweet syndrome in a 5-year-old girl (2018)
Sweet syndrome, also known as acute febrile neutrophilic dermatosis, is an infrequent dermatological disorder in pediatrics. Clinically it is characterized by the development of papular and/or nodular lesions of a reddish-violet coloration with local hypersensitivity. We report the case of a 5-year-old female who consulted 1 month after the appearance of the lesion in the nasal arch. A skin biopsy was performed and it reported diffuse dermatitis with a predominance of neutrophil polymorphonuclear cells, epidermal necrosis and absence of vasculitis. No microorganisms were identified. It was considered compatible with Sweet syndrome. It is important to consider this diagnosis in similar clinical cases and other more frequent diagnoses must be ruled out first. © 2018 Sociedad Argentina de Pediatria. All rights reserved.